Archaeometallurgical survey in the area of Masafi (Fujairah, UAE): preliminary data from an integrated programme of survey, excavation, and physicochemical analyses - Goy, Julie; Le Carlier de Veslud, Cécile; Degli Esposti, Michele; Attaelmanan, A.G. (Proceedings of the Seminar for Arabian Studies, 2013)
Archaeological investigations in the Fujairah Emirate have revealed an extensive use of copper and copper alloys, witnessed on many sites of different periods. Two of these sites, Bithnah and Masafi, were extensively excavated by the French Archaeological Mission in the UAE, which discovered substantial evidence of occupation dated to the Iron Age. On the other hand, the mineralogical richness of the Emirates' territory, particularly as concerns possible copper ore-bearing veins, is evident on the geological map and is readily traceable on the ground. Following the preliminary results of a short survey conducted by A. Ploquin and M. Ohnenstetter in 2001, two more comprehensive campaigns of survey were carried out in 2009 and 2011 with the aim of recording archaeological sites showing traces of copper production. Twelve sites related to copper exploitation were visited. They indicate different steps in copper working, from mining activities to object fabrication. The results of these surveys are presented here, together with the first analytical data on the chemical signature of ingots and artefacts retrieved at Masafi, obtained by ICP-AES and XRF. These results are discussed in the light of existing comparable data on the Iron Age metallurgy in south-eastern Arabia.